A Scheme For Space-Time-Frequency Coding And Adaptive Multiple Antenna Selection For Improving The Performance Of Multiple-Input Single-Output Ofdm System - Noordin, Nor Kamariah (2006)
In this thesis, issues such as link adaptation that include adaptive spatial mode in the context of orthogonal frequency division multiplexing (OFDM) is addressed, particularly in a multiple-input single-output (MISO) configuration suitable for mobile communications. The performances of ST- and SF-OFDM incorporating channel coding are extensively investigated in the presence of channel fading and noise. Realizing that ST and SF behave differently in different environments, a new adaptive spatial mode (ASM)-OFDM is proposed. This scheme selects the mode of transmission based on the instantaneous signal to noise ratio (SNR) for a MISO system. A new adaptive multiple antenna selection (AdMAS) using second-order moment of the channel impulse response between multiple transmitting antennas and a single receiver MISO-OFDM configuration is also proposed as a major contribution. This scheme employs a space-time-frequency coding with a symbol rate of ¾, using orthogonal signals, to avoid high complexity in detection. In the proposed AdMAS scheme the worst faded channel(s) is(are) adaptively turned off based on the calculated second-order moment of the channel impulse response. Findings show that the proposed scheme outperforms other multiple antenna schemes such as the one based on the mean of the channel impulse response, especially at higher order modulation. Throughout the simulation, channel state information (CSI) is assumed to be known both by the transmitter and the receiver which may be achieved via a dedicated feedback channel or through the reciprocity of the channel such as that found in time division duplex (TDD) system.